RESOLUSI KONFLIK DALAM PENYELESAIAN SENGKETA TANAH ADAT DAYAK KANAYATN DI DESA SUNGAI AMBAWANG KABUPATEN KUBU RAYA - NIM. A1012221033, SYAIDHINA MUZAKAR (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Land owned by Indigenous communities is regulated in their respective customary laws. Customary land is land owned by a customary legal community unit. The land ownership system according to customary law that can be owned by indigenous people can occur through clearing forests, inheriting land, receiving land through gifts, exchanges or grants, expiration/verjaring. In the past, the determination of land boundaries was generally only based on non-permanent boundaries such as rivers, trees, and other plants, agreements on determining these boundaries were generally made and there was no written agreement between the bordering areas. Based on the formulation of the problem, namely: